2022
DOI: 10.1016/j.ymssp.2021.108201
|View full text |Cite
|
Sign up to set email alerts
|

Ensemble of recurrent neural networks with long short-term memory cells for high-rate structural health monitoring

Abstract: The deployment of systems experiencing high-rate dynamic events, such as hypersonic vehicles, advanced weaponry, and active blast mitigation systems, require high-rate structural health monitoring (HRSHM) capabilities in the sub-millisecond realm to ensure continuous operations and safety. However, the development of high-rate feedback systems is a complex task because these dynamic systems are uniquely characterized by (1) large uncertainties in their external loads, (2) high levels of non-stationarity and he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…To address the second and third challenges of lack of physics and inconsistency of the data observations, approaches may include developing physics-enhanced machine learning (PEML) models, which integrates the learning model with any known physics. Machine learning using data-based methods alone currently prove very powerful tools for predicting remainable useful life for rotational machinery [18,19] and prediction of high-rate dynamics [20]. Additional current trends include PINN (physical-informed neural networks), physics-informed machine learning (PIML) [21], and digital twin interpretability [22].…”
Section: Technical Approachesmentioning
confidence: 99%
“…To address the second and third challenges of lack of physics and inconsistency of the data observations, approaches may include developing physics-enhanced machine learning (PEML) models, which integrates the learning model with any known physics. Machine learning using data-based methods alone currently prove very powerful tools for predicting remainable useful life for rotational machinery [18,19] and prediction of high-rate dynamics [20]. Additional current trends include PINN (physical-informed neural networks), physics-informed machine learning (PIML) [21], and digital twin interpretability [22].…”
Section: Technical Approachesmentioning
confidence: 99%
“…A key challenge in data-based formulations is in data scarcity arising, because high-rate experiments are expensive to conduct and may only include limited dynamic responses. 7 To address this issue, several studies proposed the use of transfer learning to train algorithms. 8,9 Of interest, recurrent neural networks are promising for modeling and predicting time series due to their sequential organization, but they face the challenge of vanishing gradient issues.…”
Section: Introductionmentioning
confidence: 99%
“…11 In particular, the authors have previously shown promise in forecasting non-stationary time series in high-rate systems by decomposing the nonstationary system into stationary systems and combining predictions from an ensemble of RNNs using a weighted sum. 7 The focus of this paper is the real-time state estimation of dynamic systems using data-based techniques to map time series measurements to structural states using TDA features, emphasizing the novel application of these features as input to recurrent neural network (RNN) algorithms. The objective of this approach is to improve the predictive capabilities of the RNNs using physical insights provided by TDA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This family of algorithms has gained tremendous popularity due to prominent applications in language modelling and machine translation [25]. Basic RNN algorithms are notoriously difficult to train, and more elaborate algorithms are commonly used instead, such as the Long Short-Term Memory Networks (LSTMs) [26] and the Gated Recurrent Units (GRUs) [27]. In this research, sequence modelling algorithms are integrated into the encoder and decoder of the denoising autoencoder to build a deep denoising autoencoder used for gas turbine gas path measurement noise filtering.…”
Section: Introductionmentioning
confidence: 99%